Persepsi Peserta Didik Terhadap Pelaksanaan Program Gerakan Seniman Masuk Sekolah - Dara Hayfa Dita; Berchah Pitoewas; Hermi Yanzi (FKIP Unila, 2018)
This study aimed to investigate and explain students’ perception towards the implementation of artist goes to school movement program at SMA YP Unila Bandar Lampung. In this research, the writer used quantitative descriptive research method with 777 respondents of population number and 77 respondents of sample. Data collecting technique used in this research was questionnaire and its supporting technique were interview and documentation. Data analysis technique used were interval formula and percentage. The result of this research showed that indicator of understanding was the highest result with as much as 68,83% or 53 out of 77 respondents were categorized as positive criteria, indicator of hope obtained a percentage result as much as 55,84% or 43 out of 77 respondents were categorized as good. However, indicator of response obtained a percentage result as much as 38,96% or 30 out of 77 respondents were categorized as negative criteria or less supportive. This was because the students were reluctant to participate on the implementation of artist goes to school movement program (GSMS) coupled with the lack of students’ knowledge about cultural values and their love to local cultural arts.Penelitian ini bertujuan untuk mengetahui dan menjelaskan persepsi peserta didik terhadap pelaksanaan program gerakan seniman masuk sekolah (GSMS) di SMA YP Unila Bandar Lampung. Dalam penelitian ini penulis menggunakan metode penelitian deskriptif kuantitatif dengan jumlah populasi 777 responden dan sampel 77 responden. Pengumpulan data yang digunakan adalah angket dan teknik penunjangnya adalah wawancara dan dokumentasi. Teknik analisis data menggunakan rumus interval dan persentase. Hasil penelitian menunjukkan pada indikator pemahaman merupakan hasil persentase tertinggi yakni sebanyak 68,83 % atau 53 dari 77 responden masuk dalam kriteria positif, pada indikator harapan diperoleh hasil persentase sebanyak 55,84% atau 43 dari 77 responden dikategorikan baik. Namun pada indikator tanggapan diperoleh hasil persentase sebanyak 38, 96% atau 30 dari 77 responden masuk dalam kriteria negatif atau kurang mendukung. Hal ini dikarenakan peserta didik yang enggan dalam mengikuti pelaksanaan program gerakan seniman masuk sekolah (GSMS) ditambah dengan minimnya pengetahuan peserta didik mengenai nilai-nilai budaya dan kecintaannya terhadap seni budaya lokal.Kata kunci: GSMS, persepsi, peserta didik.